Analisis Pengelolaan, Pengawasan dan Retribusi Parkir dalam Meningkatkan PAD - Pertiwi Pertiwi; Elmira Febri Darmayanti; Ana Septiani (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
This research aims to analyze parking fees in increasing the Local Revenue (PAD) of Metro City, as well as to identify the obstacles in its management. This research uses a qualitative method with a descriptive approach. The Metro City Government manages 53 roadside parking points and 101 special parking points. However, the management of parking fees is not yet optimal due to obstacles such as discrepancies in the names of parking attendants and the low public awareness of paying these fees. The efforts made by the government to optimize parking fee revenue include strengthening collection regulations, but supervision remains limited. Parking fees make a significant contribution to the PAD of Metro City, but there is a need for improvement in the aspects of supervision and law enforcement so that the revenue potential can be maximized. Therefore, it is important for the local government to improve the parking fee management system and raise public awareness regarding the obligation to pay these fees